A fatal case of infective endocarditis complicated by acute COVID-19 pneumonia. Issue 11 (28th December 2021) - Pandey, Anmol; Davies, William R; Calvert, Patrick A
ABSTRACT: A 74-year-old man with no co-morbidities presented to hospital with a 3-day history of diarrhoea and vomiting. He met the modified Duke's criteria for definite infective endocarditis and was immediately started on an intravenous antibiotic. Over Days 1–9, he developed renal failure. On Day 10, he was transferred to a tertiary hospital for mitral valve replacement. However, he tested positive for SARS-CoV-2 on arrival at the tertiary hospital, which delayed his surgery. He underwent bi-weekly nasopharyngeal swabs for SARS-CoV-2 with a plan to operate as soon as he tested negative, or as soon as his incubation period for COVID-19 pneumonia had elapsed. Unfortunately, he died on Day 31 from acute respiratory distress syndrome secondary to COVID-19 pneumonia. We describe the challenges in deciding on the optimal timing for valve replacement. We conclude by suggesting that earlier valve replacement may result in better outcomes.